Conclusions or Open Closures on the Teaching of Philosophy in Costa Rica: Undisciplining Teaching to Achieve the Liberation of the Educational Subject - Gómez Torres, Juan Rafael (2018)
After this tour of various topics that revolve around the theme of Pedagogy in the teaching/learning process of Philosophy, we can reach the following conclusions about the need and urgency of undisciplining teaching, the above as a closure, but being clear that we are not making an epistemological lock but an ethical-political opening of Pedagogy itself: